SCIENTIFIC-THEORETICAL VIEWS OF LOCAL BUDGET REVENUE FORECASTING IN UZBEKISTAN (Proceedings of International Educators Conference, 2024)
In the article, the analysis of scientific and theoretical views on forecasting local budget revenues is an important research direction of state finance. This includes forecasting the future revenue of local government budgets, which is essential for effective resource planning and allocation. The study includes a critical review of various theoretical perspectives and empirical studies related to local budget revenue forecasting. In general, the analysis of scientific and theoretical perspectives on forecasting local budget revenues provides valuable insights and recommendations for policymakers and practitioners to improve forecasting methods and strate.